COMPARATIVE ANALYSIS OF THE STRUCTURE AND CONTENT OF THE CURRICULUM OF LEADING US BUSINESS SCHOOLS (Pedagogy of Higher and Secondary Education, 2010)
The importance of considering the US business schools experience when building and improving the native system of business education is substantiated Goals and objectives of business education are clarified. Comparative analysis of the leading US business schools curriculum structure and content is presented in the paper. On the basis of the research conducted, recommendations on Ukrainian business education improvement are suggested.
Keywords: business education; business school; Master of Business Administration (MBA); curriculum; structure; content